1 - Vingt-Deux ans après, «l'Afrique noire est mal partie», l'histoire a-t-elle donne raison à Rene Dumont? - LAM, Aboubacry Moussa (Africa Development, 1984)
In this paper , the author is trying to findout whether the pred tions of the famous french agricultural economist Rene DUMONT come true. Indeed , this scholar predicted in his book «L'Afrique Noire mal partie» that the development of agriculture as it has been conceiv in Africa since the early days of independence by the newly created st and their partners will not solve the problems of underdevelopment w Africa was going through. These predictions which have also been made various other researchers both from Europe and North America are pro true since Africa is now undergoing a severe development crisis. This crisis is originating mainly from tne food and agricultural deficiencies. author focuses his analysis on three major african countries , Senegal , I Coast and Nigeria to check how far DUmONT's predictions have come true in these countries. Then he goes on explaining why such crisis has happ ed. At this point he recalls and criticises the various causes given in t World Bank Report. In his conclusion he insists particularly on the fact that we should learn from the experience of Europe uihich contains some u informations. This should be complemented by some resources of our own.